QRIS BEHAVIORAL INTENTION: PERCEIVED EASE OF USE, PERCEIVED USEFULNESS, DAN TRUST - Savina Meisya Rachma (2023)
This study aims to test the technology acceptance model (TAM), namely perceived ease of use, perceived usefulness, and trust on behavioral intention to use QRIS. The population in this study are people domiciled in DKI Jakarta aged 18 to 65 years who have used the QRIS payment system in the last 6 months. The sample in this study were 100 people with purposive sampling method. This study uses the Partial Least Square Structural Equation Modeling (PLS-SEM) method to analyze the data. The results of this study indicate that perceived ease of use and perceived usefulness affect behavioral intention to use. On the other hand, trust has no effect on behavioral intention to use.